Characterization of the pyrogallol-phloroglucinol isomerase of Eubacterium oxidoreducens. - Krumholz, L R (1988)
Cell extracts of Eubacterium oxidoreducens, in the presence of dimethyl sulfoxide, catalyzed the conversion of pyrogallol to phloroglucinol with methyl sulfide as a product. The isomerization reaction also proceeded when 1,2,3,5-benzenetetrol was present rather than dimethyl sulfoxide. An assay to quantitate this activity was developed. The assay followed the disappearance of 1,2,4-benzenetriol as determined colorimetrically after incubation with sodium molybdate at neutral pH. The products of this reaction were resorcinol and 2,6-dihydroxyquinone. The enzyme(s) catalyzing this reaction was purified fivefold from cells grown on gallate plus H2. The purification procedure involved treatment with 40% acetone, precipitation with ammonium sulfate, DEAE-cellulose chromatography, concentration by ultrafiltration (molecular weight cutoff, greater than 100,000), and hydroxylapatite chromatography. This preparation had a specific activity of 14.7 mumol/min per mg of protein and a pH optimum of about 7.3. It was strongly inhibited by p-chloromercuribenzoate. The mechanism of the reaction involved oxidation of the pyrogallol followed by introduction of water. The benzenetetrol intermediate was then reduced and dehydrated to phloroglucinol.